Medición de niveles de colinesterasas eritrocitarias en agricultores usuarios de plaguicidas y en practicantes de agroecología, San Cristóbal, Medellín, Colombia (2019)
ABSTRACT: To analyze erythrocyte cholinesterase values as biomarkers of exposure to pesticides (organophosphates and carbamates) and their possible effects on their users and agroecology practitioners’ health in the village of San Cristóbal, Medellín, Colombia. Methodology: Cross-sectional study in which a sample of 40 farmers was measured to see the presence of this biomarker. The measurement was then compared to demographic information, description of agricultural practices, and clinical examinations. Results: Depending on the erythrocyte cholinesterase levels in subjects who use or do not use pesticides, results showed a significant value in those who do not use them (p = 0.042). Results between women using pesticides modifying cholinesterase levels and those not using them were not statistically significant (p > 0.05). On the contrary, results in men were significant (p < 0.032). However, no statistically significant differences in erythrocyte cholinesterase levels were found between the groups of pesticide users and agroecology practitioners. An important finding was a deficient use of personal protective gear and poor technical supervision of proper use of pesticides. No symptoms associated with pesticide poisoning were found at the moment of data collection. Conclusions: Pesticides users inhibiting cholinesterase presented lower cholinesterase erythrocyte levels compared to those who practiced agroecology. The use of protection gear was poor. Therefore, this population should improve protection measures and promote more health and environmentally friendly agricultural practices, such as agroecology.